From LBK to SBK: Pottery, Bones, Lithics and Houses at the Neolithic site of Hrdlovka, Czech Republic - Vondrovský, Václav; Beneš, Jaromír; Divišová, Michaela; Kovačiková, Lenka; Šída, Petr (De Gruyter Open Ltd., 2016)
The paper is focused on the period of cultural change at the turn of 6th and 5th millennia BC, when the uniform Linear Pottery Culture (LBK) occupying an extensive area disintegrated in several local groups or cultures, including the Stroked Pottery Culture (SBK) emerging in the regions of Bohemia and Saxony. The data comprising pottery, animal bones, lithics, as well as architectural attributes from Hrdlovka site, situated in northwest Bohemia, are presented. In accordance with the sites of Hrbovice-Chabařovice and Dresden-Prohlis a rather uninterrupted LBK/SBK transition has been observed, which contrasts with the image of “LBK crisis” observed in other regions. Lithics production and distribution networks of raw material seem to be stable. The change in stockkeeping strategies correlating with the transitional period are considered rather as modification of local environmental conditions. On the level of households, a similar architectural development has been documented at the Hrdlovka and Dresden-Prohlis sites. The processes of LBK/SBK transition in terms of cultural change are also discussed.
Od LnK k StK: keramika, kosti, kamenná industrie a domy na neolitickém sídlišti Hrdlovka, Česká republika
Keywords: Neolithic longhouse, ceramic analysis, chipped stone industry, animal bones, culture change, northwest Bohemia; Neolitický dlouhý dům, analýza keramiky, štípaná industrie, zvířecí kosti, kulturní změna, severozápadní Čechy